DRAFTING DEFINITIONS WITH POLISEMY AND SEMANTIC CHANGE IN MIND - Carney, Terrence R (Obiter, 2023)
Legislative definitions must be as clear and precise as possible. Different sources for legislative drafting provide guidelines on how to ensure clarity and precision. Many of these guidelines provide language-related advice. However, language guidelines and linguistic principles are not the same thing. Garth Thornton’s book is one of the few that suggests drafters study language to benefit their drafting techniques. He specifically mentions the link between language and society, and claims that drafters will gain by understanding how meaning (and language) change owing to societal changes. This article explores Thornton’s observation by attending to the polysemy and possible semantic change of the word “strike”, taken from the case of SASRIA v Slabbert Burger Transport [2008] ZASCA 73. The article claims that social processes like lived experiences and changing perspectives function as drivers of semantic change. These changes lead to the development of new semantic variations that coexist with the old or base meaning of a word, resulting in polysemy. Polysemy has the potential to cause vagueness, ambiguity and uncertainty, which complicates drafters’ task in producing clear and precise texts. Understanding the complexity and instability of words ahead of time could aid drafters to hone their definitions for better legal communication. To prevent unnecessary semantic pitfalls, the contribution further suggests that drafters apply their linguistic awareness (referred to as the “lexicological approach”) to words chosen for definition, as well as to a selection of words deliberately left undefined.